(Invited) CH3NH3PbI3 Perovskite Solar Cells on Inorganic Materials: CuSCN and Crystal Silicon. (10th September 2015) - Ito, Seigo
Abstract : Organo-lead halide perovskites have attracted much attention for solar cell applications due to their unique optical and electrical properties. With either low-temperature solution processing or vacuum evaporation, the overall conversion efficiencies of perovskite solar cells with organic hole-transporting material were quickly improved to over 15% during the last 3 years. However, the organic hole-transporting materials used are normally quite expensive due to complicated synthetic procedure or high-purity requirement. Here, we demonstrate the application of an effective and cheap inorganic p-type hole-transporting material, copper thiocyanate, on lead halide perovskite-based devices. With low-temperature solution-process deposition method, a power conversion efficiency of 12% was achieved under full sun illumination. Moreover, PECVE-free c-Si solar cells will be presented for utilization of tandem device with perovskite solar cells.